New insights into the structure of the Earth`s crust on- and offshore Northern Victoria Land, Antarctica, by means of gravimetric and magnetic 3D modelling - Schindler, Peter (2016)
Victoria Land, Antarctica, has been in the focus of German scientists for more than 30 years now. Many expeditions have been undertaken to reveal the geologic structures and clarify the geodynamic processes, which have led to the present situation. An important part in the exploration is taken by geophysical measurements, as such measurements can be carried out in places, where no outcrops exist. Thus it is possible to connect distant outcrops through glaciated areas, or extend geologic knowledge to off-shore regions. Over the past decades, especially aeromagnetic measurements have been carried out extensively. The present study for the first time combines the existing aeromagnetic data to a large data set, almost completely covering Victoria Land. These data were complemented by a gravimetric anomaly generated from a global gravity field model. With subsequent 3D modelling it was possible to develop an idea of the crustal structures in Victoria Land. The gravimetric model shows a distinct mountain root below the Transantarctic Mountains. As these result from rifting processes, the presence of a mountain root is not to be expected. This root most probably is a remnant of the early paleozoic, accretionary Ross orogen which forms part of the basement of the Transantarctic Mountains. Especially in northern Victoria Land, the model is characterized by basement highs and lows, which follow the course of known fault zones, but are anti-correlated to existing graben structures.The magnetic model, which is limited to the northern coastal area along the Penell and Oates Coast and George V Land, shows a North-South striking basement high in the West, with gentle slopes to the West and East. The basement high coincides with a basement high from the gravimetric model and the Rennick graben, a prominent graben structure; it is, therefore, also anti-correlated. Other structural features known from geology are not obvious in the magnetic model. Victoria Land in der Antarktis ist seit mehr als 30 Jahren ein Schwerpunkt ...